Image denoising using wavelet transform and CUDA - Hovhannes M. Bantikyan (АН Арм. ССР)
The discrete wavelet transform has a huge number of applications in science,engineering, mathematics and computer science. Most notably, it is used for signal coding to represent a discrete signal in a more redundant form, often as a preconditioning for data compression. Beginning in the 1990s, wavelets have been found to be a powerful tool for removing noise from a variety of signals (denoising). In this paper the implementation of DWT (Discrete Wavelet Transform)-based denoising algorithm in parallel manner on Graphics Processing Unit is presented, using the CUDA technology.
Keywords: Mathematics; Computer software